Ink-based transparent compliant electrode for direct coating on untreated hydrophobic PDMS surface - Shrestha, Milan (2024)
Polydimethylsiloxane (PDMS) is widely used as the substrate for wearable sensors and elastomeric actuators because of its good dielectric property, stretchability, thermal/chemical resistance, biocompatibility, and transparency. PDMS-based stretchable sensors and electroactive actuators need a coating of thin compliant electrodes. However, PDMS is hydrophobic with water contact angle above 120°. Such low surface energy of PDMS creates issues for uniform coating of ink-based electrodes and/or their adhesion. Similarly, metal thin-film or nanowire-based materials coated on PDMS easily peels off. Surface treatments like UV/plasma exposure can temporarily increase PDMS's surface energy. However, these surfaces return to its original state within hours leaving behind a brittle surface layer that cracks upon stretching. To address these issues, we formulated a viscous composite ink with PEDOT:PSS and PDMS that can easily be coated on untreated PDMS by blade casting, screen printing, and so on. These coatings are highly transparent, stretchable, electrically conductive and work as compliant electrodes. We fabricated transparent dielectric elastomer actuators by coating PEDOT:PSS/PDMS composite ink on Elastosil (PDMS) substrates. The actuation strain and breakdown-fields were slightly lower compared to DEA with conventional graphite electrodes. However, the additional self-clearing capability of PEDOT:PSS/PDMS electrodes enhanced robustness of the DEA in events of localized dielectric breakdown.